Maryam's Rebellion Against The State Reflected At Okky Madasari's The Outcast Novel An Individual Psychological Approach - Indra Mukti, Abdullah, Dr. Phil. Dewi Candraningrum, M.Ed, Titis Setyabudi, S.S. M. Hum (2015)
The major problem in this study is how the major character proves her faith and rebellion against the state in The Outcast (2014) novel by Okky Madasari. This study focused on one of the major characters namely Maryam, using the means of individual psychology analysis. The object of this study is Okky Madasari The Outcast novel published in 2014 by Gramedia pustaka. The type of this study is descriptive qualitative. The primary data source is the novel The Outcast itself and the secondary data source is books or any information related to the practice of faith, marriage norm and rebellion against the state that support the individual psychology approach by Adler. The technique of analyzing data in this research paper is descriptive. The researcher concludes that rebellion against the state and faith is the individualemotions, it drives from system of personality. When the psychological analysis shows that person switched her identities coming from her inferiority of feeling and fictional finalism has pushed her to do some efforts to attain the superiority and she must sacrifice everything.Finally, the psychological analysis shows that the human factor will exchange their characters because the activating personalityaspects within the characters and the cause are among other family and enviromental factors. Okky Madasari gives the important points when the majorcharacter, Maryam, gets the conflict between her inferiority and superiority to prove her love.The outcome of the study shows that the problem faced by the major character Maryam causes the conflict of her mental condition. It comes because her struggle to prove her faith and love for her life. Finally, her effort makes her suffer until the end.